Nanostructure silver absorbance with polarized light spectroscopy (PLS) and mobile imaging - Liu, Xinzhi; Shafie, Suhaidi (Taylor and Francis Ltd., 2024)
This study presents a novel interdisciplinary approach for characterizing the optical properties of nanostructured silver films, combining methodologies from polarized light spectroscopy (PLS) and mobile app-based spectroscopic image detection. Silver nanofilms were deposited using electron beam evaporation (EBE) and subsequently analyzed for their absorbance across the visible light spectrum through PLS spectroscopy. The innovative aspect of this study lies in the validation of PLS spectral data using a mobile application developed with MIT App Inventor, which analyzes the intensity of light beams captured in images taken by a smartphone. The findings indicate that the silver nanofilm exhibits peak absorbance at approximately 400 nm within the violet region, corroborated by the mobile app’s data, which shows the lowest light intensity. However, discrepancies were observed from 500 to 600 nm, likely due to ambient light interferences and inherent optical phenomena such as diffraction, reflection, and refraction. Despite these deviations, the app’s readings closely align with the PLS data, supporting the film’s selective absorption properties. This study demonstrates the potential of this multidisciplinary technique in nanomaterial research, highlighting the application of nanotechnology in material science and the transformative potential of integrating software engineering for in-depth material characterization. These findings open avenues for advancements in both academic and practical applications.